2014
DOI: 10.1039/c4tb00216d
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots prepared from ginger exhibiting efficient inhibition of human hepatocellular carcinoma cells

Abstract: Fluorescent carbon nanodots (C-dots; 4.3 AE 0.8 nm) from fresh tender ginger juice provide high suppression of the growth of human hepatocellular carcinoma cells (HepG2), with low toxicity to normal mammary epithelial cells (MCF-10A) and normal liver cells (FL83B). The inhibition is selective to HepG2 over other tested cancer cells, including human lung cancer cell line (A549), human breast cancer cell line (MDA-MB-231), and human cervical cancer cell line (HeLa). Western blot results reveal that the C-dots up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
151
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(175 citation statements)
references
References 42 publications
7
151
0
2
Order By: Relevance
“…In fact, very recently Pierrat et al claimed that the toxicity of C-dots is mainly determined by the synthesis protocol [30]. Also, it has been reported that some food-based C-dots show anticancer properties, which strongly relies on the starting material employed for the synthesis [3132]. Keeping the aforementioned fascinating medicinal activities of selected spices in mind, highly fluorescent C-dots have been synthesized by a green one-pot hydrothermal route, using cinnamon, red chilli, turmeric and black pepper as starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, very recently Pierrat et al claimed that the toxicity of C-dots is mainly determined by the synthesis protocol [30]. Also, it has been reported that some food-based C-dots show anticancer properties, which strongly relies on the starting material employed for the synthesis [3132]. Keeping the aforementioned fascinating medicinal activities of selected spices in mind, highly fluorescent C-dots have been synthesized by a green one-pot hydrothermal route, using cinnamon, red chilli, turmeric and black pepper as starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…There are several kinds of raw materials for CDs, such as ginger, straw, coffee, egg, candle ash, and grapheme [11,12]. The CDs prepared have been found to have good inhibitory effects on the growth of and antioxidation of hepatocellular carcinoma, lung cancer, breast cancer, and human cervical cancer [2,13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the charcoal ash is a typical carbonized traditional Mongolian medicine [2]. As a matter of fact, the carbonized medicine is made up of carbon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, C-Dots becomes an attraction because it has a very large potential for application of photocatalysis, bioimaging and optoelectronic (Li et al, 2012). C-Dots can be produced simply through the process of hydrothermal with various types of sources of carbon such as citric acid, soy milk, orange juice, ginger, food waste, waste paper etc (Rahmayanti et al, 2015;Zhu et al, 2012;Sahu et al, 2012;Li et al, 2014;Park et al, 2014;Wei et al, 2014). The process of hydrothermal cause carbon chains suffered the polymerization processes and forming particle C-Dots.…”
Section: Introductionmentioning
confidence: 99%